Transdisciplinary research approaches for crop science research: theory, practice, and implications for research design - Najjar, Dina; Amoak, Daniel; Belcher, Brian (2024)
Presentation on: Transdisciplinary research approaches for crop science research: theory, practice, and implications for research design.